Do Social Pension Schemes Promote the Mental Health of Rural Middle-Aged and Old Residents? Evidence From China - Pan, Guochen; Li, Shaobin; Geng, Zhixiang; Zhan, Kai (Frontiers in Public Health, 2021)
As China experiences rapid aging, the mental health of older rural adults has become a major public health concern. Among other social insurance programs, the New Rural Social Pension (NRSP) scheme was established to replace part of the income for old-age rural residents in China. This article employs survey data from the China Health and Retirement Longitudinal Study (CHARLS) in 2015 and 2018 to investigate the impact of a pension on depression in middle-aged and old residents. Our results show that the pension scheme not only reduces the depressive symptoms of the rural residents but keeps down the prevalence rate of depression. Among the subscribers of the pension scheme, the pensioners benefit more from enrolling in the pension scheme than the contributors in terms of depression alleviation. The impact of pension on depression displays heterogeneity; female residents, residents in central China, and/or those from lower income households are found to be positively affected. It is also confirmed that a pension scheme contributes to easing depression via reduced labor supply, better family support, and more consumption expenditure. JEL Classification: H55, I18, I38.